1992
DOI: 10.2527/1992.70102935x
|View full text |Cite
|
Sign up to set email alerts
|

Use of melengestrol acetate and gonadotropins to induce fertile estrus in seasonally anestrous ewes

Abstract: Ewes of three genotypes (Hampshire, n = 59; Rambouillet, n = 36; crossbred, n = 57) were used to determine the efficiency of melengestrol acetate (MGA) and(or) PG-600 (a combination of pregnant mare's serum gonadotropin and human chorionic gonadotropin) in inducing fertile estrus in seasonally anestrus ewes. Ewes were assigned randomly, within genotype, to treatments in a 2 x 2 factorial arrangement. Treatments were control, .125 mg of MGA given twice per day for 9 d (MGA), a single 5-mL injection of PG-600 (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 22 publications
5
44
1
1
Order By: Relevance
“…In this study, prolificacy rate (number of lambs born/number of ewes lambing) did not different among groups which were 1.0 in the three groups and therefore the use of PMSG had no effects on increasing lambs born. This opinion is consistent with what Safranski et al (1992) reported, the number of lambs born per ewe lambing (prolificacy rate) was not different among treatments or genotypes. Consequently, the advantage that was obtained in ovulation rate through the use of PG-600 was not realized at lambing, although the number of luteal structures increased when PG-600 was injected on the last day of feeding MGA, the number of lambs born per ewe was not significantly affected.…”
Section: Wwwijeabcom Page | 1279supporting
confidence: 93%
See 2 more Smart Citations
“…In this study, prolificacy rate (number of lambs born/number of ewes lambing) did not different among groups which were 1.0 in the three groups and therefore the use of PMSG had no effects on increasing lambs born. This opinion is consistent with what Safranski et al (1992) reported, the number of lambs born per ewe lambing (prolificacy rate) was not different among treatments or genotypes. Consequently, the advantage that was obtained in ovulation rate through the use of PG-600 was not realized at lambing, although the number of luteal structures increased when PG-600 was injected on the last day of feeding MGA, the number of lambs born per ewe was not significantly affected.…”
Section: Wwwijeabcom Page | 1279supporting
confidence: 93%
“…Our results of lambing rate were higher than those obtained in control, MGA and MGA+PG 600 groups (14.8, 40.5 and 41.2%, respectively) according to Safranski et al (1992). But close to those obtained by (Windorski et al, 2008) who found that lambing rate in Rambouillet ewes was 80.4, 77.8 and 80.4% in control, MGA and MGA+PG-600, respectively.…”
Section: Wwwijeabcom Page | 1279supporting
confidence: 75%
See 1 more Smart Citation
“…600 only, had significantly reduced mating rates (6.6%) when compared to ewes receiving both MGA and P.G. 600 (69.8%, Safranski et al, 1992). Ovulation rate can be increased through the administration of P.G.…”
Section: Gonadotropinsmentioning
confidence: 90%
“…600. Safranski et al (1992) documented that P.G. 600 when coupled with an MGA treatment lasting 10 d had no beneficial effects on conception rate and number of lambs born per ewe.…”
Section: Gonadotropinsmentioning
confidence: 99%